Accumulation and Distribution of Natural Gas Reservoir in Volcanic Active Area: A Case Study of the Cretaceous Yingcheng Formation in the Dehui Fault Depression, Songliao Basin, NE China. (30th September 2021) - Zeng, Fancheng; Liu, Bo; Zhang, Changmin; Zhang, Guoyi; Gao, Jin; Liu, Junjie; Ostadhassan, Mehdi
Abstract : Tight gas sandstone and volcanic gas reservoirs have received global attention in the energy arena for further exploration and exploitation attempts. Considering the Yingcheng Formation of Dehui fault depression in the Songliao Basin as an example, this study focused on the accumulation and distribution of natural gas reservoirs in volcanic area in a fault depression basin. Volcanic activities occurred in the Yingcheng Formation, which is distributed centrally in the northwest of the study area. During the sedimentation of the Yingcheng Formation, fan-delta, lacustrine, and nearshore subaqueous fan facies were deposited. The source rocks of the Yingcheng Formation have high abundance of organic matter mainly in type III at high-overmature stages, indicating favorable conditions for gas production. The porosity of volcanic reservoir is 3.0%-14.8%, the permeability is 0.0004 mD-2.52 mD, and the pore types are mainly secondary dissolved pores and fractures. Besides, the porosity of the tight sandstone reservoir is 0.5%-11.2%, and the permeability is 0.0008 mD-3.17 mD. The pore types are mainly interparticle pores, with a small proportion of intraparticle pores and microfractures. The intrusion of late volcanic magma provided sufficient heat for the thermal maturity progression of organic matter in Yingcheng Formation and promoted the generation of natural gas in large quantities. Volcanic rocks formed at the early and middle stages of volcanic activities occupied the sedimentary space and hindered the development of sedimentary sand bodies to a certain extent. However, volcanic rocks can become the seal to promote the formation of tight sandstone gas traps. Comparing tight sandstone reservoirs with volcanic ones, the latter are less affected by compaction; thus, their petrophysical properties do not vary much with depth, showing more homogeneous characteristics. The pyroclastic rocks influenced by volcanic activity and the secondary pores formed by dissolution in the later stages also provide reservoir space for gas accumulation. Ultimately, the tight sandstone and volcanic rocks in the study area form a complex gas reservoir system, which can become a reference for exploration and exploitation of natural gas in other petroliferous fault depressions that are affected by volcanisms.